Hypsometric analysis for estimating the geomorphological evolution of the Yurma, Mariscal Luzuriaga and Yungay river sub-basin (Áncash, Peru) (Aporte Santiaguino, 2025)
The hypsometric behavior of the Yurma River sub-basin, located in the provinces of Mariscal Luzuriaga and Yungay (Áncash), was analyzed with the aim of estimating its geomorphological evolution. A non-experimental, cross-sectional, descriptive research design was applied, using geospatial data processed with ArcGIS 10.8.2 software. The results show that the hypsometric integral is 0,427 and the maximum hypsometric deviation is 0,184, indicating that the sub-basin is in a mature geomorphological stage, with partially eroded relief that is still hydrologically functional. These indicators reflect moderate erosion potential and relatively stable tectonic dynamics. It is concluded that hypsometric analysis constitutes an evaluation method to estimate the degree of geomorphological evolution of basins, as well as for territorial and environmental planning.
Keywords: Dimensionless hypsometric curve; Hypsometric integral; Maximum deviation; Geomorphological evolution